An artificial somatic reflex arc - He, Ke (2020)
The emulation of human sensation, perception, and action processes has become a major challenge for bioinspired intelligent robotics, interactive human-machine interfacing, and advanced prosthetics. Reflex actions, enabled through reflex arcs, are important for human and higher animals to respond to stimuli from environment without the brain processing and survive the risks of nature. An artificial reflex arc system that emulates the functions of the reflex arc simplifies the complex circuit design needed for "central-control-only" processes and becomes a basic electronic component in an intelligent soft robotics system. An artificial somatic reflex arc that enables the actuation of electrochemical actuators in response to the stimulation of tactile pressures is reported. Only if the detected pressure by the pressure sensor is above the stimulus threshold, the metal-organic-framework-based threshold controlling unit (TCU) can be activated and triggers the electrochemical actuators to complete the motion. Such responding mechanism mimics the all-or-none law in the human nervous system. As a proof of concept, the artificial somatic reflex arc is successfully integrated into a robot to mimic the infant grasp reflex. This work provides a unique and simplifying strategy for developing intelligent soft robotics, next-generation human-machine interfaces, and neuroprosthetics.